Kann Ignatianische Kontemplation Erkenntnisse liefern? - Niederbacher, Bruno (Zeitschrift für katholische Theologie, 2017)
The aim of this article is to understand how Ignatian Contemplation can yield cognitions. The first part analyses the processes that are, according to the exercises of Ignatius von Loyola, involved in Ignatian Contemplation. The second part deals with epistemological questions by investigating the cognitive role of imagination, emotion and desire.